LIQUIDITY AND ADOPTION OF PUBLIC PRIVATE PARTNERSHIPS IN KENYAN PUBLIC UNIVERSITIES - ASAKANIA, FRANCIS MUKATIA (Machakos University Press, 2021)
Traditionally the role of infrastructure provision was solely undertaken by the government. However over time most governments especially in the developing world have continued to experience increasing budget deficits in meeting their infrastructure needs. Such increasing budget deficits lead to reduced allocation to public entities such as public universities. In order to bridge this funding gap, private sector players are brought on board through public private partnerships. Kenyan public universities have in the recent past experienced difficulties in meeting their short term obligations as they fall due. This is partly attributable to reduced capitation in comparison to the increasing costs of running the university. The study aimed at assessing how the need for liquidity influences adoption of public private partnerships in Kenyan public universities. The specific objectives of this study were to evaluate the extent to which need for timely payment of short term external and internal liabilities influence the adoption of public private partnerships in Kenyan public universities. The study employed a descriptive research design with a target population of 223 comprising of purposively selected management representatives from nine public universities. The sample size was 143. Data was collected using a structured questionnaire. The response rate attained was 86%. Statistical Package for Social Sciences (SPSS) was employed in data analysis. The findings indicated that need for timely payment of short term internal and external liabilities had a statistically significant influence on adoption of public private partnerships. Based on the study findings it was concluded that need for timely payment of short term obligations had a significant positive influence on the level of adoption of public private partnerships in Kenyan public universities. It is therefore recommended that Kenyan public universities should make use of public private partnerships in order to maintain a sound liquidity level since it ensures regular small periodic cash out flows as opposed to heavy lump sum cash outflow that is characteristic of traditional funding. Since liquidity is just one of the financial drivers of public private partnerships, it is suggested that other studies could be done on the other drivers.
Keywords: Liquidity; Adoption; Equity; Debt; Capital